1989
DOI: 10.2170/jjphysiol.39.67
|View full text |Cite
|
Sign up to set email alerts
|

Opioid involvement in the perception of pain due to endurance exercise in trained man.

Abstract: The purpose of this study was to evaluate the role of endogenous opiates in modulating physical performance during dynamic exercise in conscious man. The plasma concentration of fl-endorphin (BEP) and of adrenocorticotropic hormone (ACTH) along with muscle pain (McGuill Pain Questionnaire) were assessed in 17 trained, male runners before and after running the longest possible distance within 12 min (i.e., the Cooper test). Each runner participated twice in the test (double-blind cross-over design), with a 1-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Exercise of sufficient intensity and duration results in the release of peripheral and central beta-endorphins which have been associated with changes in pain sensitivity. 15,55,57,64 However, animal research has provided the most consistent support for this hypothesis 23,64 , while the human data has been mixed. 6,18,31,52 Animal data also shows that non-opioid systems exist (e.g., endocannabinoid, neurotransmitters such as serotonin and norephinephrine) and that parameters of the exercise (i.e., duration of session, continuous vs. intermittent, and varying water temperature for swim protocols) may determine which system is activated.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise of sufficient intensity and duration results in the release of peripheral and central beta-endorphins which have been associated with changes in pain sensitivity. 15,55,57,64 However, animal research has provided the most consistent support for this hypothesis 23,64 , while the human data has been mixed. 6,18,31,52 Animal data also shows that non-opioid systems exist (e.g., endocannabinoid, neurotransmitters such as serotonin and norephinephrine) and that parameters of the exercise (i.e., duration of session, continuous vs. intermittent, and varying water temperature for swim protocols) may determine which system is activated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that peripheral measurements of endorphins provide only limited information about central opioidergic mechanisms underlying psychophysiological effects. This also seems to apply to receptor blocking studies, which are not summarized here in detail, but which have also revealed equivocal results, ie, either negative3235 or positive blocking effects in the pain domain 3,36. On the other hand, several studies have reported positive blocking effects in the mood domain,3,37,38 thus supporting the hypothesis of central opioidergic effects mediating mood enhancement.…”
Section: Link Between Peripheral Beta-endorphin Levels and Mood And Pmentioning
confidence: 55%
“…Endocannabinoids are also thought to play a role in runner's high [36]. Paulev et al [37] compared naloxone (0.8 mg i.v.) to placebo during a Cooper test (running the longest possible distance within 12 min) in trained subjects.…”
Section: Discussionmentioning
confidence: 99%